Childhood dietary trajectories and adolescent cardiovascular phenotypes: Australian community-based longitudinal study. Issue 14 (27th June 2018) - Kerr, Jessica A; Gillespie, Alanna N; Gasser, Constantine E; Mensah, Fiona K; Burgner, David; Wake, Melissa
Abstract: Objective: With the intention to inform future public health initiatives, we aimed to determine the extent to which typical childhood dietary trajectories predict adolescent cardiovascular phenotypes. Design: Longitudinal study. Exposure was determined by a 4 d food diary repeated over eight waves (ages 4–15 years), coded by Australian Dietary Guidelines and summed into a continuous diet score (0–14). Outcomes were adolescent (Wave 8, age 15 years) blood pressure, resting heart rate, pulse wave velocity, carotid intima-media thickness, retinal arteriole-to-venule ratio. Latent class analysis identified 'typical' dietary trajectories from childhood to adolescence. Adjusted linear regression models assessed relationships between trajectories and cardiovascular outcomes, adjusted for a priori potential confounders. Setting: Community sample, Melbourne, Australia. Subjects: Children ( n 188) followed from age 4 to 15 years. Results: Four dietary trajectories were identified: unhealthy (8 %); moderately unhealthy (25 %); moderately healthy (46 %); healthy (21 %). There was little evidence that vascular phenotypes associated with the trajectories. However, resting heart rate (beats/min) increased ( β ; 95 % CI) across the healthy (reference), moderately healthy (4·1; −0·6, 8·9; P =0·08), moderately unhealthy (4·5; −0·7, 9·7; P =0·09) and unhealthy (10·5; 2·9, 18·0; P =0·01) trajectories. Conclusions: Decade-long dietary trajectories did not appear to influence macro- or microvascular structure or stiffness by mid-adolescence, but were associated with resting heart rate, suggesting an early-life window for prevention. Larger studies are needed to confirm these findings, the threshold of diet quality associated with these physiological changes and whether functional changes in heart rate are followed by phenotypic change.